DYNAMIC LEXICO-SEMANTIC DIALECT FEATURES IN THE MICROTEXTES OF «GALYCKO-RUSSIAN FOLK TALES», GATHERED BY I. FRANKO IN THE DIALECTS OF THE PRECARPATHIAN AREAL - Бігусяк, М. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article describes the lexical-semantic peculiarities of the Boyk, Hutsul, Pokut, Transdniestrian and transitional dialects, which are reflected in the body of Franko paremias, recorded in 120 settlements of these regions. The article focuses on the thematic analysis of the conjectures from the perspective of the mentality of their carriers and linguistic comments by the author of the collection.